Language, culture and cognition from Descartes to Lewes - Kaitaro, Timo (Leiden : Brill, 2022)
This volume describes how the significance of language and culture in forming human cognition has been understood from the mid-sixteenth century to the mid-nineteenth century. It discusses thinkers who realized that the human mind—and brain—is in fact a cultural artefact and that language is not merely a means to communicate thoughts, but also to form them in the first place. It presents a novel perspective on the history of philosophy in which the narrative is no longer centered on the question of whether knowledge results from experience or reason, but whether experience and reason are in fact possible without language.
The natural and artificial body in Cartesian philosophy -- Hobbes and the citizens of the realm of truth -- Locke : combining ideas with a little help from words -- Leibniz, Wolff, and symbolic cognition in the German tradition -- Daniel Defoe and the wild boy -- Hume and the artificial in human understanding -- Condillac and Diderot on the role of artificial signs in cognition -- La Mettrie : man as an artefact -- The nature of morality : Diderot, Helv etius and Rousseau -- Maupertuis and the debates in the Berlin Academy -- Herder : from the language of a silent loner to human perfection -- Hamann and the primacy of language and tradition -- The id eologues : the semiotics and physiology of culture -- The divine origins of language -- Back to the institutions of nature : Gall and Spurzheim -- Humboldt : language and the creation of national character -- G.H. Lewes and symbolic thought -- Conclusions : from the institutions of nature to history and culture.
Kuvailun perustana verkkoaineisto; nimeke PDF-nimiösivulta (Brill, katsottu 25.10.2022).
Keywords: kieli ja kielet; filosofia; kielifilosofia; kulttuuri; kognitio; Language and languages -- Philosophy -- History; Language and culture -- History; Cognition and culture -- History; Philosophy, Modern; e-kirjat